Gastritis Stages in Monozygotic and Dizygotic Dyspeptic Twins - Mindaugas Urba; Jurgita Skieceviciene; Dainius Janciauskas; Laimas Jonaitis; Limas Kupcinskas; Matteo Fassan; Massimo Rugge; Juozas Kupcinskas (Gastroenterology Research and Practice)
Background. The progression of Helicobacter pylori-associated gastritis towards atrophic gastritis is modulated by host-related and environmental factors. Studies that explore the possible involvement of host-related versus environmental factors in the development of gastritis phenotype induced by H. pylori are highly needed. Aims. Our study was aimed at investigating the phenotype of H. pylori-associated gastritis in two cohorts of monozygotic and dizygotic twins, using the OLGA/OLGIM gastritis staging system. Methods. Two cohorts of monozygotic (14 pairs) and dizygotic (15 pairs) dyspeptic twins prospectively underwent endoscopy with biopsy sampling based on Sydney protocol. H. pylori status and OLGA/OLGIM stages were assessed and compared. Results. The mean age of monozygotic and dizygotic twins was 40.4 and 38.6 years, respectively (p=0.623). The overall prevalence of H. pylori infection was 51.7%. Among the 14 monozygotic twin pairs, five pairs were H. pylori-positive, four were H. pylori-negative, and five were H. pylori-discordant. Among the 15 dizygotic twin pairs, five pairs were H. pylori-positive, five were H. pylori-negative, and five were H. pylori-discordant. Concordance for antrum atrophy in monozygotic twins was 78.6% (11/14 pairs) and in dizygotic twins 73.3% (11/15 pairs) (p=0.742). Concordance for corpus atrophy in monozygotic versus dizygotic twins was 92.9% (13/14 pairs) and 86.7% (13/15 pairs), respectively (p=0.584). Concordance for antrum intestinal metaplasia (IM) in monozygotic twins was 85.7% (12/14 pairs) and in dizygotic 73.3% (11/15 pairs) (p=0.411). Concordance for corpus IM in monozygotic twins was 85.7% (12/14 pairs) and in dizygotic 86.7% (13/15 pairs) (p=0.941). Among monozygotic and dizygotic subjects, the stage of gastritis was concordant in both H. pylori-positive and H. pylori-negative subjects. Conclusions. In conclusion, histological gastric mucosa alterations in monozygotic and dizygotic twins showed high rates of concordance. Furthermore, OLGA/OLGIM gastritis stages were not modulated by the zygosity of the twins.